LOSSES INCURRED IN SOYBEAN DEPENDING ON THE WATER CONTENT AT GRAINS HARVEST - Galindo, Fernando Shintate; Zocoler, João Luis; Teixeira Filho, Marcelo Carvalho Minhoto; Buzetti, Salatiér; Santini, José Mateus Kondo; Boleta, Eduardo Henrique Marcandalli; Ludkiewicz, Mariana Gaioto Ziolkowski (REVISTA DE AGRICULTURA, 2019)
The objective of this work was to study the ideal water content at grains at harvest of soybean crop, yield and production components as well as losses from natural drying in the field at different water contents at grains harvest. The experimental design was of randomized blocks with 4 repetitions and the treatments consisted in the harvest of the following average levels of water contents of grains on a wet basis: 37.9 (point of full physiological maturity), 20.2, 18.7, 15.6, 14.4, and 13.1%. The final population of plants, 100-kernel weight and potential yield of grains linearly decreased with the reduction of grain moisture content at harvest, however, the anticipation of the soybean harvest causes higher losses, with ideal harvesting point close to 13% moisture (W.B.).